Graphic design process : from problem to solution : 20 case studies - Skolos, Nancy (Laurence King Pub. Co., 2012)
This book "features a series of in-depth case studies exploring a range of both universal and unique design methods. Chapters investigate typical creative strategies--Research, Inspiration, Drawing, Narrative, Abstraction, Development, and Collaboration--examining the work of twenty-three graphic designers from around the world."--Page 4 of cover